Conditioned place preference successfully established in typically developing children - Hiller, Leah Ticker; Takata, Sandy; Thompson, Barbara L. (Frontiers in Behavioral Neuroscience, 2015)
Affective processing, known to influence attention, motivation and emotional regulation is poorly understood in young children, especially for those with neurodevelopmental disorders characterized by language impairments. Here we faithfully adapt a well-established animal paradigm used for affective processing, conditioned place preference for use in typically developing children between the ages of 30-55 months. Children displayed a conditioned place preference, with an average 2.4 fold increase in time spent in the preferred room. Importantly, associative learning as assessed with conditioned place preference was not correlated with scores on the Mullen Scales of Early Learning, indicating that conditioned place preference can be used with children with a wide range of cognitive skills.